(untitled) (Universitas Scientiarum, 2014)
Analyzing asymmetry in species associated with disturbed environments enables the evaluation of the morphological plasticity of generalistic species and the different evolutionary responses of sexes or populations to environmental or genetic stress. This report is a study of the cranial and mandibular asymmetry of Colombian Artibeus lituratus. This species has a wide distribution and high abundance, but its morphological plasticity remains uncertain. We characterized its presence, fluctuating asymmetry, directional asymmetry and antisymmetry by measuring 11 craneometric traits in 146 adults from different localities. Fluctuating asymmetry was present in all traits; directional asymmetry and antisymmetry in three; and no measurement error in any trait. Females showed more fluctuating asymmetry in the splachnocranium and males in the neurocranium. Traits with functional importance while biting had lower levels of asymmetry and higher similarity. Traits with antisymmetry did not show association while traits with directional asymmetry showed mandibular association. We discuss the relation between the presence of cranial and mandibular asymmetry, with the functional similarity of different traits.